Persepsi dan Minat Generasi Muda Terhadap Profesi Pengrajin Suji: Sebuah Analisis Korelasi - Kurnia Intan Permata; Febby Febriyanti; Ilma Islami; Muhammad Ibrahim Ismail; Rahmat Yanuar; Fiham Afwan Mu’arij (JSEP (Journal of Social and Agricultural Economics), 2023)
The young generation as the successor to the sustainable development of suji plants will be examined for their perceptions and interests as a solution to the phenomenon of regeneration in agriculture. This research aims to analyze the perceptions and interests of the younger generation towards the suji craftsman profession and the relationship between the perceptions of the younger generation towards suji craftsmen with an interest in developing the suji craftsmanship profession. The research methods used were surveys, interviews, and field observations. Sampling was carried out using a simple random sampling method to 100 young generation respondents (15-25 years) in Sudajaya Girang Village. The analytical method used is descriptive qualitative, cross-tabulation, descriptive statistics, and Spearman's rank correlation. The young generation's perception of the suji craftsman profession is positive with a score of 2,76 out of 4 (good category). The interest of the younger generation in the development of the suji craftsman profession is positive with a score of 2,7 out of 4 (interesting category) because the suji craftsman profession is considered to have a lot of potential to be developed in the future. The relationship between perception and interest in the profession of suji craftsmen has a positive relationship at strong intervals.